Interference and Electromagnetic Compatibility Challenges in 5G Wireless Network Deployments - Idrissa Abubakar; Jafri Din; Manhal Alhilali; Hong Yin Lam (Institute of Advanced Engineering and Science, 2017)
5G wireless network technology is going operate within the environment of other electrical, electronic and electromagnetic devices, components and systems, with capability of high speed data connectivity acting as network transceiver stations with Massive MIMO for Internet of Things (IoT). Considering the level of interoperability, electromagnetic Interference and electromagnetic compatibility to avoid electromagnetic pulse effects (EMP) which is capable of not only causing network malfunctions but total devices and equipments failure in mission critical operations, like hospital MRI scan machines, security profiling and data handling or even personal healthcare devices like heart pacemaker. Electromagnetic energy coupling in PCB due to: radiation, reflection and Crosstalk generates reliability challenges affecting Signal Integrity between traces of multilayer boards stalks, power bus and packaging creating Electromagnetic interference (EMI) in PCB leading false clock response to system failure. Above were considered very essential when deploying 5G wireless network facility as presented in this paper.